The challenges of managing a patient with concurrent pulmonary tuberculosis and sarcoidosis (a case report) - R. V. Tarasov; S. S. Sadovnikova; E. V. Krasnikova; L. N. Lepekha; A. N. Tikhonskaya; E. V. Ertseva; M. A. Bagirov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Tuberculosis and sarcoidosis are granulomatous diseases and can cause similar symptoms. In addition, both diseases can affect the lungs, whаt makes difficult to diagnose them differentially. An observation from practice is given: staged surgery of a patient with a combination of sarcoidosis and pulmonary tuberculosis. Patient M., 34 years old, contact with a tuberculosis patient has not been established. A CT scan of the chest organs in January 2021 revealed changes in the lungs. Upon further examination: the sample with the tuberculosis recombinant allergen was negative, Mycobacterium tuberculosis (MBT) was not detected in the sputum analysis. A video-assisted lung biopsy (atypical S2 right lung resection with paratracheal lymphadenectomy) was performed. The morphological picture corresponded to sarcoidosis in the active phase of the process. The primary care pulmonologist prescribed Metipred at a dose of 12 mg. In November 2021, after of decrease in the dosage of Мetipred, the patient noted a severe paroxysmal cough. The patient was examined again :tuberculin skin-test dated 06/14/2022 - papule of 12 mm, sputum analysis from 06/23/2022 revealed MBT DNA with preserved drug sensitivity to all anti-tuberculosis drugs. When sowing on dense nutrient media, growth of MBT was detected. According to the CT scan of the chest dated 08/18/2022, consolidated inflammation in the upper lobe on the right lung, interstitial changes and lymphadenopathy of the intrathoracic lymph nodes (IGLU) were detected. On 10/20/2022 he entered CTRI Federal State Budgetary Budgetary Educational Institution regarding infiltrative tuberculosis of the right operated lung. An individual chemotherapy regimen had been prescribed. He received methylprednisolone 12 mg for 1 month, then the dose was reduced to 8 mg. During the control after 2 months, bacterial excretion stopped, but there was a negative X-ray dynamic as appearance of fresh focal shadows. The dosage of Methylprednisolone has been increased to 12 mg. The control showed positive clinical and radiological dynamics after 4 months. In order of local sanitation and reducion the time of drug treatment resection of the right lung (upper lobectomy and part of the S4 with partial pleurectomy) was performed. DNA of MBT and acid-fast mycobacteria ++ were found in the resection material. Histologically, the phase of mild progression of the tuberculosis process was identificated. In order to reduce оverstretching of the remaining parts of the right lung and reduce the risk of progression of tuberculosis, extrapleural thoracomyoplasty with resection of the I-IV ribs and removal of a group of paratracheal lymph nodes was performed after 1 month. Histological examination of the lymph nodes revealed granulomatosis without necrosis. The dosage of methylprednisolone was reduced to 8 mg 1 month after surgery. With a control CT scan of chest after 3 months, there was a negative X-ray dynamic, despite the ongoing TB therapy according to sensitivity MBT data. The changes were regarded as destabilization of the course of sarcoidosis, which was confirmed by the results of histological examination of lymph nodes and negative microbiological studies on MBT of them. The patient resumed taking meteliprednisolone at a dosage of 12 mg, and underwent an extracorporeal methods course to induce remission of sarcoidosis and potentiate the effect of corticosteroids. After 6 months, there was a positive trend in the form of partial resorption of focal changes. The patient returned to his usual lifestyle.